Comparison on Tree Height-Stem Diameter Allometric Equations and Biomass Carbon Estimation of Two Dry Dipterocarp Forests in Northern Thailand - Phongkhamphanh, Teuanchay; Khamyong, Soontorn; Sri-ngernyuang, Kriangsak (KKU Science Journal, 2018)
The tree height-stem diameter (H-D) allometric equations and tree biomass carbon estimation of two dry dipterocarp forests (DDF) in northern Thailand, were compared. Study areas included two sites, the Huai Hong Khrai Royal Development Study Center (Site 1) and the Mae Tha sub-district community forest (Site 2). Twelve sampling plots, each of size 40 x 40 m, were used for tree survey at Site 1 and fifteen plots for Site 2, and the plots were arranged in the both study area by a random sampling method. Tree data were obtained by measuring stem diameters at breast height (DBH) 1.3 m above ground in all sample plots, and total heights of all trees that height over 1.5 m were measured in 11 plots for Site 1 and 5 plots for Site 2 using a Measuring Pole Height Stick and Haga hypsometer. The stem diameter and tree heights of 9 dominants tree species were used for making H-D allometric equations of each site, and apply it for calculate tree biomass within the plots. Some different biomass amounts were obtained from the equations of same species and the two-site of DDF. These species included Shorea obtusa, Shorea siamensis, Dipterocarpus obtusifolius, Dipterocarp tuberculatus, Pterocapus macrocarpus, Dalbergia assamica-Dalbergia oliveri, Canarium subulatum, Aporosa villosa, and Gluta usitata. The H-D allometric equations of these species in the two sites indicated some differences of biomass and carbon stock in the forests. The heights of most mature dominant tree species in Site 1 were lower than Site 2, except for Pterocarpus macrocarpus, Canarium subulatum and Gluta usitata. Application of the H-D allometric equations of one site to another caused the different estimation of biomass and carbon stock found in the forest. average carbon stock in tree biomass of Site 1 calculated using the equations of Site 2 showed overestimation, 44.77±5.39 to be 48.73±5.88 (+3.96 Mg ha-1) while turnover biomass of Site 2 obtained by using the equations of Site 1 presented lower estimation, 61.97±26.61 to be 59.57±25.05 (-2.70 Mg ha-1). However, these differences were not significant statistic.